DIGITALIZATION OF CRYPTOSPHERE OF THE EAEU COUNTRIES: STATUS AND PROSPECTS - O. Makhalina (Publishing House of the State University of Management, 2019)
The advantages of cryptocurrency, its distribution and application experience in different countries have been considered. The results of the analysis of the state and ways of development of national and supranational cryptocurrencies in the countries of the Eurasian Economic Union (Armenia, Belarus, Kazakhstan, Kyrgyzstan, Russia) have been introduced. Conclusions and recommendations have been formulated: 1.it is necessary to develop a single regulatory framework for the regulation of the crypto sphere in the EAEU countries. 2.digitalization of the cryptosphere should be carried out according to the General scheme; 3.to make maximum use of blockchain technology to create a digital economy in the EAEU countries.